The Male Athlete Triad - A consensus statement from the female and male athlete triad coalition part 1: Definition and scientific basis - Nattiv, A.; De Souza, M. J.; Koltun, K. J.; Misra, M.; Kussman, A.; Williams, N. I.; Barrack, M. T.; Kraus, E.; Joy, E.; Fredericson, M. (Clinical Journal of Sport Medicine, 2021)
The Male Athlete Triad is a syndrome of 3 interrelated conditions most common in adolescent and young adult male endurance and weight-class athletes and includes the clinically relevant outcomes of (1) energy deficiency/low energy availability (EA) with or without disordered eating/eating disorders, (2) functional hypothalamic hypogonadism, and (3) osteoporosis or low bone mineral density with or without bone stress injury (BSI). The causal role of low EA in the modulation of reproductive function and skeletal health in the male athlete reinforces the notion that skeletal health and reproductive outcomes are the primary clinical concerns. At present, the specific intermediate subclinical outcomes are less clearly defined in male athletes than those in female athletes and are represented as subtle alterations in the hypothalamic-pituitary-gonadal axis and increased risk for BSI. The degree of energy deficiency/low EA associated with such alterations remains unclear. However, available data suggest a more severe energy deficiency/low EA state is needed to affect reproductive and skeletal health in the Male Athlete Triad than in the Female Athlete Triad. Additional research is needed to further clarify and quantify this association. The Female and Male Athlete Triad Coalition Consensus Statements include evidence statements developed after a roundtable of experts held in conjunction with the American College of Sports Medicine 64th Annual Meeting in Denver, Colorado, in 2017 and are in 2 parts—Part I: Definition and Scientific Basis and Part 2: The Male Athlete Triad: Diagnosis, Treatment, and Return-to-Play. In this first article, we discuss the scientific evidence to support the Male Athlete Triad model.